Sharing individual knowledge collectively: a theoretical framework for emerging knowledge organisations - Barker, Rachel (Department of Communication Science, University of the Free State, 2016)
Scant attention has been paid to the role of individual employees in the knowledge management discourse, even though knowledge is recognised to be rooted in the individual. Where organisational theorists believe that the collective knowledge of individuals needs to be managed, it is only possible if knowledge leaders emerge as change agents to facilitate knowledge creation and sharing. Hence an excessive focus in the knowledge management literature recently acknowledged the appropriation of individual knowledge through participation as distinct from knowledge practice focusing on managers or leaders who choose how to manage knowledge. The commonality of most recent research indicates an emphasised focus on knowledge management and knowledge leaders to implement strategic integrated communication to assist with the creation of knowledge organisations. Where knowledge management focuses on human capital and knowledge based theory, strategic integrated communication emphasises that knowledge leaders should acknowledge the premises of the strategic intent of knowledge organisations through the management of information, innovation, creativity, cultural phenomena, participation and inputs from the environment based on trust, loyalty, integrity and credibility. This forms the basis to address the research problem that, despite the tremendous research opportunities to examine these constructs, limited research has been conducted from evolving organisational and knowledge leadership perspectives.
Keywords: Knowledge management; Change agents; Organisational leadership; Strategic integrated communication